Beyond the known phenotype of sotos syndrome: a 31-individuals cohort study - Lourdes, Vega-Hanna; Mario, Sanz-Cuesta; Didac, Casas-Alba; Mercè, Bolasell; Loreto, Martorell; Leticia, Pías; Lucia, Feller Ana; Martínez-Monseny, Antonio Federico; Mercedes, Serrano (Frontiers in Pediatrics, 2023)
Sotos Syndrome (SS, OMIM#117550) is a heterogeneous genetic condition, recognized by three main clinical features present in most cases: overgrowth with macrocephaly, typical facial appearance and different degrees of intellectual disability. Three different types are described caused by variants or deletions/duplications in NSD1, NFIX and APC2 genes. We aimed to describe a cohort of pediatric patients reporting the typical and unexpected findings in order to expand the phenotype of this syndrome and trying to find genotype-phenotype correlations. In our referral center, we collected and analyzed clinical and genetic data of 31-patients cohort diagnosed with SS. All of them presented with overgrowth, typical dysmorphic features and different degree of developmental delay. Although structural cardiac defects have been reported in SS, non-structural diseases such as pericarditis were outstanding in our cohort. Moreover, we described here novel oncological malignancies not previously linked to SS such as splenic hamartoma, retinal melanocytoma and acute lymphocytic leukemia. Finally, five patients suffered from recurrent onychocryptosis that required surgical procedures, as an unreported prevalent medical condition. This is the first study focusing on multiple atypical symptoms in SS at the time that revisits the spectrum of clinical and molecular basis of this heterogeneous entity trying to unravel a genotype-phenotype correlation.